Does Financial Education Impact Financial Literacy and Financial Behavior, and If So, When? - Kaiser, Tim (World Bank, Washington, DC, 2017)
A meta-analysis of 126 impact evaluation studies finds that financial education significantly impacts financial behavior and, to an even larger extent, financial literacy. These results also hold for the subsample of randomized experiments (RCTs). However, intervention impacts are highly heterogeneous: financial education is less effective for low-income clients as well as in low- and lower-middle income economies. Specific behaviors, such as the handling of debt, are more difficult to influence and mandatory financial education tentatively appears to be less effective. Thus, intervention success depends crucially on increasing education intensity and offering financial education at a "teachable moment."